Tingkat konsumsi garam beryodium dan kaitannya dengan gangguan akibat kekurangan yodium ibu hamil - Tri Endang Irawati; Hamam Hadi; Untung Widodo (Jurnal Gizi Klinik Indonesia, 2011)
Background: Iodine deficiency disorders (IDD) is one of main nutrition problems which cannot be eliminated until now in Indonesia. Total goiter rate (TGR) of school children increased from 9.8% in 1998 to 11.1% in 2003. In Gunung Kidul District, TGR of school was 12.2% and of pregnant mothers was 18.4% in 1996. One of efforts to overcome IDD is salt iodization. Result of a national survey of household iodized salt consumption in 2002 showed that only 68.53% of households consumed sufficient level of iodized salt, while salt monitoring at Gunung Kidul District in 2003 showed that only 73.08% of households consumed sufficient level of iodized salt. The low rate of consumption level of iodized salt may be caused by availability of salt with low iodine level (not as high as mentioned in the label), higher price of iodized salt and lack of knowledge about types and benefits of iodized salt among mothers.Objective: To identify consumption level of iodized salt and IDD status of pregnant mothers at IDD endemic area at Gunung Kidul District.Method: The study was an observational type which used cross sectional design with both quantitative and qualitative approaches. Subject of the study were pregnant mothers at their second trimester pregnancy.Results: Availability of iodized salt according to: quality was 81.1% low and 18.9% sufficient; types of salt was 17.6% coorse, 77.8% bricket, and 4.6% fine salt; price was 69.0% high and 31.0% not high; taste was 36.8% bitter and 63.2% not bitter. Analysis result of Pearson Chi-Square with Odds Ratio showed that there was relationship between quality and types of salt with consumption level of iodized salt in the household (p<0.05) with OR=20.50 for quality, and OR=43 for types. There was relationship between salt consumption level of urine iodine excretion with p<0.05 and OR=2.604. Median of urine iodine excretion level was 86.1µg/l which belonged to category of light IDD endemic area and there had been no change of endemic area status since 1996.Conclusion: There was significant relationship between quality and types of salt with consumption level of iodized salt. There was relationship between iodized salt consumption level and IDD. Iodized salt program was not yet effective and supply of iodine capsules should go on until it reached use of good iodized salt.